Diversity of Butterflies in Ledokombo Hillocks Jember, East Java, Indonesia - Husni Mubarok; Alfina Eka Dwi Candra; Bayu Sandika; Wiwin Maisyaroh; Ellena Yusti; Agmal Qodri (Journal of Tropical Biodiversity and Biotechnology, 2023)
Ledokombo hillocks are small hills located in Jember, East Java that have natural resources and face habitat alteration such as plantation and mining.  However, a study of the diversity of butterflies has not been carried out in this area. We analysed the diversity of butterflies using the Shannon-Wiener diversity index (H’) and Pielou evenness index (E).  We identified 514 individuals from 34 species and demonstrated a moderate diversity of butterflies (H'= 1.907) in this area. Our study results could be used for sustainable ecological management of plantations in Ledokombo Hillocks, Jember, East Java.